Pengaruh Biaya Produksi Dan Biaya Operasional Terhadap Laba Bersih - Ester Meafrida Wati Pasaribu; Nanu Hasanuh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study is to determine the effect of production costs and operating costs on net income in the consumer goods industry sector for the 2015-2019 period. The sample selection uses a sampling technique. In order to obtain a sample of 15 companies and a total of 75 data. The regression analysis analysis method used is multiple linear regression analysis through classical assumption tests and hypothesis testing. Based on the results of this study indicate that partially production costs have an effect on net income and other research results partially operational costs have a significant effect on net income. Simultaneously, production costs and operating costs have a significant influence on net income Keywords: Production Costs, Operational Costs, and Net Profits